CONHECIMENTOS DOCENTES: UMA ANÁLISE DOS DISCURSOS DE PROFESSORES QUE ENSINAM MATEMÁTICA - Dionizio, Fátima Aparecida Queiroz (2013)
This study presents an analysis of pedagogical, curricular and content knowledge that teachers of mathematics in basic education, in Ponta Grossa/PR have on Trigonometry. Empirical data was obtained with the use of a tool containing different kinds of errors made by students in Trigonometry exercises to be analyzed and point out possible intervention by the teachers as well as to present responses to Trigonometry concepts. This data was analyzed based on Shulman’s (1986,2001) theoretical contributions and on the functions and discursive operations according to the Register of Semiotic Representation theory by Raymond Duval (2004, 2009, 2011). The research question was: How is knowledge about Trigonometry characterized and what is the nature of the knowledge related to learning issues and Trigonometry teaching presented by mathematics teachers who work in basic education? And the objectives of the study were: to characterize the knowledge of Trigonometry of mathematics teachers working in basic education and; to reveal the nature of mathematics teachers’ knowledge in relation to Trigonometry learning and teaching issues.The research had a qualitative approach, with descriptive and elucidative characteristics, and the analysis methodological procedures were assisted by Bardin’s (2009) content analysis. The organization of data was carried out with the aid of the software Atlas.ti, through which the subject content knowledge, the pedagogical knowledge of content, and the curricular knowledge were gathered within the discourse expansion function proposed by Duval (2004) for later analysis. The results of this study indicate that teachers’ knowledge that was more evident was the knowledge of the subject content. These results point to the need for teachers to be more attentive to other aspects of knowledge also necessary to their education practice and which seem to have been disregarded.